INNOVATIVE MARKETING APPROACHES IN TОURISM (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article analyzes the activity of the tourism sector of Ukraine and the results of an online survey before the velvet season on traveling in Ukraine during a full-scale war. The regions of Ukraine with a significant increase in budget revenues from tourism entities are identified. The essence of tourism marketing is defined. The most important features of tourist demand formation are characterized. The essence of the tourism product is presented and its typical features are highlighted. New trends in tourism in connection with active digitalization are considered: «e-tourism» (ETravel), «virtual tourism», «tourist information systems». The importance of virtual tourism in the context of restrictions on the mobility of tourists, as well as innovative tourist products created using Internet technologies: augmented and virtual reality, QR codes, online booking, touch screens, geoportals, quest tours are determined.The article provides an interpretation of marketing communications in tourism and presents innovative marketing communications in tourism. The challenges of Russia's full-scale invasion of Ukraine, which have changed the main trends in the innovative development of the tourism sector, are considered.The top 10 startups in the travel industry are highlighted: Holidify, Bikemap, Tripoto, PickYourTrail, ClickBus, Hundredrooms, Zostel, Trawell.in, GoRaymi, Journi. The ranking is based on the startup’s place in the global startup ranking. The advantages and functional purpose of Ukrainian startups in the field of tourism are characterized: Bookimed, 2event, Silence, Viaguide.
Keywords: tourism marketing, innovative tourism product, innovative marketing communications, tourism startups.